Oxidative Stress-Induced Cellular Senescence: Is Labile Iron the Connecting Link? - Lambros Nousis; Panagiotis Kanavaros; Alexandra Barbouti (Antioxidants, 2023)
Cellular senescence, a cell state characterized by a generally irreversible cell cycle arrest, is implicated in various physiological processes and a wide range of age-related pathologies. Oxidative stress, a condition caused by an imbalance between the production and the elimination of reactive oxygen species (ROS) in cells and tissues, is a common driver of cellular senescence. ROS encompass free radicals and other molecules formed as byproducts of oxygen metabolism, which exhibit varying chemical reactivity. A prerequisite for the generation of strong oxidizing ROS that can damage macromolecules and impair cellular function is the availability of labile (redox-active) iron, which catalyzes the formation of highly reactive free radicals. Targeting labile iron has been proven an effective strategy to counteract the adverse effects of ROS, but evidence concerning cellular senescence is sparse. In the present review article, we discuss aspects of oxidative stress-induced cellular senescence, with special attention to the potential implication of labile iron.